Nature of the System of Common Standards for Valuation in the Countries of the Eurasian Economic Union - Viktorovich, Grigoriev Vladimir (Journal of Reviews on Global Economics, 2018)
The article is devoted to the concept of a system of common valuation standards in the countries of the Eurasian Economic Union. Much attention is given to the necessity of creating a system of unified standards, its composition and structure. It is spoken in detail elements of the codification of evaluation standards. The article gives a detailed analysis of the results of implementing a system of common standards in the practice of assessing the countries of the Eurasian Economic Union.